The Influence of Transformasional Leadership Style, Organizational Justice, Employee Engagament and Employee Reaction on Employee Performance - Priska Sitorus; Sumitro Sarkum; Meisa Fitri Nasution (Budapest International Research and Critics University, 2021)
This research was conducted to determine and analyze the effect of transformational leadership style, organizational justice, employee engagement and employee reaction on employee performance. The design of this study was hypothesis testing using primary data obtained by distributing 291 questionnaires to employees of Pt Torganda's oil palm plantation with the measuring scale used is the Likert scale. The data analysis technique used was multiple linear regresion analysis quantitative data analysis techniques using statistical methods Sciens statistikal package for the social sciens (SPSS). The results of this study conclude that partially and simultaneously there is a significant and positive relationship between transformational leadership style, organizational justice, employee engagement and employee reactions to employee performance.